1997
DOI: 10.1098/rspb.1997.0180
|View full text |Cite
|
Sign up to set email alerts
|

Visual and socio–cognitive information processing in primate brain evolution

Abstract: Social group size has been shown to correlate with neocortex size in primates. Here we use comparative analyses to show that social group size is independently correlated with the size of non-V1 neocortical areas, but not with other more proximate components of the visual system or with brain systems associated with emotional cueing (e.g. the amygdala).We argue that visual brain components serve as a social information`input device' for socio-visual stimuli such as facial expressions, bodily gestures and visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 20 publications
1
76
0
Order By: Relevance
“…Research on the evolution of neocortex size often uses group size as a proxy for social complexity, and the correlation between group size and relative neocortex size is well established (Sawaguchi and Kudo, 1990;Dunbar, 1992Dunbar, , 1995Dunbar, , 1998Sawaguchi, 1992;Barton, 1996;Joffee and Dunbar, 1997). Increasing group size is presumably driven by ecological factors such as predation (van Schaik, 1983;van Schaik and van Hooff, 1983), but it is the increasingly complex social relationships that require more information processing and have selected for larger neocortices (Dunbar, 1992(Dunbar, , 1998.…”
Section: Alternative Mechanisms Of Intrasexual Competition In Haplorhmentioning
confidence: 99%
“…Research on the evolution of neocortex size often uses group size as a proxy for social complexity, and the correlation between group size and relative neocortex size is well established (Sawaguchi and Kudo, 1990;Dunbar, 1992Dunbar, , 1995Dunbar, , 1998Sawaguchi, 1992;Barton, 1996;Joffee and Dunbar, 1997). Increasing group size is presumably driven by ecological factors such as predation (van Schaik, 1983;van Schaik and van Hooff, 1983), but it is the increasingly complex social relationships that require more information processing and have selected for larger neocortices (Dunbar, 1992(Dunbar, , 1998.…”
Section: Alternative Mechanisms Of Intrasexual Competition In Haplorhmentioning
confidence: 99%
“…Dunbar [20] has specifically implicated language functions in human societies as crucial for social cohesion, yet nonverbal, emotional communication has also been implicated in social bonding [5••,22]. In fact, the part of the brain that shows the strongest relationship with group complexity is the newer region of the neocortex, not phylogenetically older regions such as the amygdala or areas of visual cortex [23]. Moreover, it has recently been suggested that maintaining group cohesion in species such as the chimpanzee, that live in a fission-fusion society (see glossary) characterized by temporal and geographical distance, is far more demanding in terms of computational and cognitive load than a group that preserves a constant grouping structure, as is found in Cercopithecines [24].…”
Section: Neural Specializations For Emotional Communication?mentioning
confidence: 99%
“…Notable exceptions are the avian studies of Lefebvre et al (3,[35][36][37][38] mentioned below. To our knowledge, despite ample evidence for links between neural measures and various lifestyles in mammals (8,9,19,22), there is no direct, unequivocal support for a link between brain size and general behavioral flexibility.…”
mentioning
confidence: 99%
“…The neural processing underlying innovation and social learning is widely thought to reside in these brain structures, collectively known as the ''executive brain'' (41,42), and it is the neocortex that has received attention from students of the social intelligence hypothesis (9). The neocortex and striatum are genomically and functionally linked, with the maternal genome making a considerable developmental contribution to these brain regions, and there have been evolutionary tradeoffs between the executive and ''emotional'' (hypothalamus, septum) brain in primates (41).…”
mentioning
confidence: 99%